Five new taxa in the genus Pinnularia sectio Distantes (Bacillariophyta) from Livingston Island (South Shetland Islands) - van De Vijver, B.; Zidarova, R. (Phytotaxa, 2011)
The non-marine diatom flora of Livingston Island (South Shetland Islands, Maritime Antarctic Region) is currently under revision. The taxonomy and morphology of all Pinnularia taxa belonging to the section Distantes present in the samples from Livingston Island have been studied. Eleven different Pinnularia taxa from this section have been recorded. In addition to the cosmopolitan Pinnularia borealis var. borealis, P. borealis var. scalaris and P. rabenhorstii and three already described (sub) Antarctic taxa (P. australorabenhorstii, P. obaesa and P. rabenhorstii var. subantarctica), five new taxa are noted here based on their unique morphological features. The new taxa are: Pinnularia australoborealis sp. nov., P. borealis var. pseudolanceolata var. nov., P. laterotundata sp. nov., P. perlanceolata sp. nov., and P. quesadae sp. nov. These results confirm the presence of a highly specific non-marine diatom flora in the Antarctic Region contradicting the view concerning diatom cosmopolitanism.